Factors Affecting Customer Trust in Chatbot Usage: Evidence from Indonesia - Amelia, Amelia; Sartika, Fani (Journal of Indonesian Economy and Business, 2025)
Introduction/Main Objectives: Customer trust is critical in ensuring the successful implementation of chatbots. Building trust is essential to ensure that users feel confident in using chatbot across various contexts, including customer service. Background Problems: Despite its importance, there is limited understanding of how specific chatbot features influence customer trust, especially within the Indonesian context. Novelty: Drawing principally on the Technology Acceptance Model (TAM), this empirical study develops and tests a model that incorporates anthropomorphism, the attribution of human-like qualities, to provide a more comprehensive explanation of customer trust. Research Methods: This study utilizes quantitative analysis of data gathered from 368 customers to examine the relationships between perceived usefulness, ease of use, anthropomorphism, and trust. A structured survey was administered, and statistical techniques were employed to validate the proposed model and determine the significance of each factor. Finding/Results: The analysis reveals that perceived usefulness, ease of use, and anthropomorphism are all significant predictors of trust in chatbots. Among these, ease of use emerges as the most influential factor, emphasizing its pivotal role in fostering trust. Conclusion: This study provides practical guidance for managers and developers aiming to design trust-enhancing chatbots. Key strategies include integrating human-like features, focusing on usability, and highlighting the practical benefits offered by chatbots. These approaches can improve customer engagement, enhance interaction quality, and support the succesful implementation of chatbot technologies in Indonesia.